Type a math problem
Solve for x

Steps by Finding Square Root
Steps by Finding Square Root
Swap sides so that all variable terms are on the left hand side.
Take the square root of both sides of the equation.
Solve for x (complex solution)

Solve for y
Assign y
Graph
Giving is as easy as 1, 2, 3
Get 1,000 points to donate to a school of your choice when you join Give With Bing
x^{2}=y
Swap sides so that all variable terms are on the left hand side.
x=\sqrt{y} x=-\sqrt{y}
Take the square root of both sides of the equation.
x^{2}=y
Swap sides so that all variable terms are on the left hand side.
x^{2}-y=0
Subtract y from both sides.
x=\frac{0±\sqrt{0^{2}-4\left(-y\right)}}{2}
This equation is in standard form: ax^{2}+bx+c=0. Substitute 1 for a, 0 for b, and -y for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{0±\sqrt{-4\left(-y\right)}}{2}
Square 0.
x=\frac{0±\sqrt{4y}}{2}
Multiply -4 times -y.
x=\frac{0±2\sqrt{y}}{2}
Take the square root of 4y.
x=\sqrt{y}
Now solve the equation x=\frac{0±2\sqrt{y}}{2} when ± is plus.
x=-\sqrt{y}
Now solve the equation x=\frac{0±2\sqrt{y}}{2} when ± is minus.
x=\sqrt{y} x=-\sqrt{y}
The equation is now solved.